2009
DOI: 10.1200/jco.2008.19.8853
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Bosutinib, Dasatinib, and Nilotinib Against 18 Imatinib-Resistant BCR/ABL Mutants

Abstract: fluorouracil, oxaliplatin, and concurrent radiation, and the toxicity profile is not impressively better or worse (it will be worse than it is currently, if the combination is adopted in a multicenter strategy) than we have reported/observed previously in most trials. Clearly, the idea that one chemoradiotherapy regimen is right for all patients is not a solution for the future. We need to garner resources to develop strategies that will allow us to optimize therapy for each esophageal patient; this is the ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
320
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(342 citation statements)
references
References 23 publications
12
320
1
7
Order By: Relevance
“…These patients are probably less likely to have ABL kinase domain mutations. In accordance with the recently reported clinical results in chronic phase patients, 21 and with a cutoff of IC 50 150 nM for mutations with a higher chance of clinical responses to nilotinib recently described by Hughes et al, 15 we found that patients harboring mutations with an in vitro moderate or high resistance to nilotinib, including E255K, Y253H, and F359V, [22][23][24][25] were less likely to respond to nilotinib, and none of the 3 T315I-positive patients responded. These mutations were also the most commonly newly acquired mutations in patients who did not respond to nilotinib or progressed during therapy.…”
Section: Discussionsupporting
confidence: 92%
“…These patients are probably less likely to have ABL kinase domain mutations. In accordance with the recently reported clinical results in chronic phase patients, 21 and with a cutoff of IC 50 150 nM for mutations with a higher chance of clinical responses to nilotinib recently described by Hughes et al, 15 we found that patients harboring mutations with an in vitro moderate or high resistance to nilotinib, including E255K, Y253H, and F359V, [22][23][24][25] were less likely to respond to nilotinib, and none of the 3 T315I-positive patients responded. These mutations were also the most commonly newly acquired mutations in patients who did not respond to nilotinib or progressed during therapy.…”
Section: Discussionsupporting
confidence: 92%
“…P-ALK value is normalized both on the untreated sample and on the total ALK level: (P-ALK treated/ P-ALK untreated) divided by (ALK treated/ALK untreated). Relative resistance (RR) index was calculated as the ratio between mutant and WT IC 50 values (32). qPCR data were analyzed using the DDCt method, normalized on the proper housekeeping gene.…”
Section: Software and Statistical Analysismentioning
confidence: 99%
“…Second-TKIs are generally well tolerated, with occurrence of grade 3/4 drug-related adverse events being less and hematological adverse event profiles being more favorable than those of imatinib. Second-TKIs also exhibit increased inhibitory potency against BCR-ABL1 kinase and efficacy in the treatment of patients with many BCR-ABL1 KD mutations that develop from imatinib use [16,24]; the T315I mutation confers resistance to both imatinib and 2nd-TKIs. Although excellent results have been reported with 2nd-TKIs, most of these were from prospective clinical trials, indicating that the data is from a selected group of patients.…”
Section: Introductionmentioning
confidence: 99%